Fenomena transverse welding pada proses ekstrusi aluminium - FIRMANDINI, DANI (2007)
Transverse Welds occur in the billet-to-billet extrusion process, which is often used in modern aluminum extrusion plants for the purpose production. The transverse weld introduces a discontinuity at the weld interface in the extruded product and in many structural applications. This is not acceptable because it can severely reduce the strength and is detrimental to the quality of the extruded product. The requirement of wasting a certain portion of the product becomes undesirable. Since the occurrence of this defect is troublesome in industrial practice, it is important to study the conditions leading to transverse welding formation. This study concentrated on improving the understanding of the behavior and the formation mechanisms of transverse welds with the aim of providing general guidance for aluminum extrusion industry. The experiment of extrusion process was undertaken in parallel with a finite element analysis (FEA) using ABAQUS software, a suite of powerful engineering simulation programs, based on the finite element method, that can solve problem ranging from relatively simple linear analysis to the most challenging nonlinear simulations, including metal forming simulation. An axisymmetric 2D geometric model of the tooling and billet was constructed for the analysis. In this work, transverse welding formation was investigated by a variation of die reduction. The influence of coefficient of friction, and punch speed were also observed. The formation and metal flow behavior of transverse welds in the aluminum extrusion process have been investigated using an FEA simulation technique. It was shown that inhomogeneous metal flow occurred and a transverse welding pattern were revealed.